Konversi Dokumentasi Keperawatan Berbasis Elektronik - Kalimah, Siti; Fitryasari P.K, Rizki; Mariyanti, Herdina (Journal of Telenursing (JOTING), 2024)
This research aims to improve the quality of nursing services, increase time and cost efficiency, optimize patient data management, improve care coordination, and provide better outcomes for patients overall. The method used was a systematic review carried out using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The databases used are Scopus, Science Direct, Pubmed and the Ners journal. The research results show that electronic-based documentation offers optimization for nurses in providing nursing care to patients. This includes more effective and efficient documentation, more integrated nursing care, and reducing the use of paper (paperless) which can contribute to reducing the impact of global warming and reducing hospital expenditure. In conclusion, changing nursing documentation in paper form to electronic documentation in hospitals requires careful preparation. Preparation for preparing the instruments used, supporting infrastructure and the readiness of nurses to carry out nursing documentation. Keywords: Nursing Documentation,Electronic Nursing Documentation